UMA REVOLUÇÃO PELO ACASO OU O CUT-UP NO CINEMA UNDERGROUND DOS ANOS 60 - Costa, Anderson (2013)
This text, besides being a thesis, is an account of a personal journey. The academic aim is to reflect on the possibilities of the Cut-Up Films produced by Antony Balch and William S. Burroughs as elements that destabilize perception in the context of the North-American society of the 1960s. In theoretical terms, this society finds itself in a crisis of meaning, triggered by the decadence of disciplinary spaces and by the appearance of systems of control, concepts here understood in the perspectives of Michel Foulcault and Gilles Deleuze. My hypothesis is that by the change in the perception we have of society, we go through a change in consciousness that is fundamental if we want to take more complex social changes into account. This possibility dialogizes with the beatnik ideals present in the countercultural movement that underlies the work of Burroughs and Balch. On the other hand, this work is also a personal journey in search of my own experiences. It is about a trip in search of an old car, which is a pretext for a parallel discussion on how attitudes can contribute, somehow, for a rupture in patterns of behavior and the dominating market laws.